2019
DOI: 10.1111/jphp.13071
|View full text |Cite
|
Sign up to set email alerts
|

A population pharmacokinetic model of vancomycin for dose individualization based on serum cystatin C as a marker of renal function

Abstract: Objectives This study aimed to establish a vancomycin population pharmacokinetics (PPK) model based on serum cystatin C and to optimize dosing for achieving targeted steady‐state trough concentrations (Css) of 10–15 and 15–20 mg/l. Methods Patients aged ≥18 years were prospectively enrolled. A vancomycin PPK model was built with glomerular filtration rate (GFR) as a renal covariate estimated by cystatin C. A new group of patients were used for external evaluation. PPK analysis and Monte Carlo simulations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 47 publications
(114 reference statements)
1
5
1
Order By: Relevance
“…Patients with a CLcr >180 mL/min do not need to increase the dose, which is consistent with the saturation correlation dimension of our model. Other studies reported higher daily doses than ours [9,12,30]. Differences in the choice of simulation target might be the reason.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Patients with a CLcr >180 mL/min do not need to increase the dose, which is consistent with the saturation correlation dimension of our model. Other studies reported higher daily doses than ours [9,12,30]. Differences in the choice of simulation target might be the reason.…”
Section: Discussioncontrasting
confidence: 49%
“…Establishing a population pharmacokinetic model is optimal for planning dosing regimen. However, most of the studies provided only regimens for patients with impaired renal function [9][10][11][12]. The pharmacokinetic profile of vancomycin in patients with ARC has not been well established and an appropriate dosing recommendation is very necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Serum cystatin C (Cys C) is a low molecular weight protein produced by all nucleated cells, and its concentration in the blood is constant and is not affected by the patient's age, body weight or sex. 5 Previous researchers have developed population pharmacokinetic models based on Cys C. [6][7][8][9] In those studies, the pharmacokinetics of vancomycin can be well predicted by the models. Other studies have also developed population pharmacokinetic models based on SCR, and the predictive performance of those models is also good.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…Across all 28 included studies, equations for SCr-and cysC-based estimates of kidney function varied [25]. Since 2017, additional literature has been published that corroborated these findings [37][38][39]. These studies were primarily pharmacokinetic associations or simulations.…”
Section: Medication Dosing Based On Cyscmentioning
confidence: 96%